Underground Storage of Natural Gas in Hydrate State: Primary Injection Stage (Global Journal of Science Frontier Research, 2018)
The paper is devoted to simulation of the initial stage of natural gas hydrate underground storage: gas injection into aquifer just below permafrost rocks. It is based on the mathematical model of multiphase non-isothermal real gas and water flow in porous media. The model takes into account the transformation of gas and water into hydrate at certain temperature which depends on gas flow pressure. The dynamics of hydrate and water saturation as well as the pressure and temperature fields in a reservoir with given porosity, permeability and initial values of pressure, temperature and water saturation have been studied. An implicit finitedifference scheme is used to approximate the original boundary-value problem. The finitedifference equations have been solved using simple iteration and sweeping algorithms. Several examples of calculations corresponding to real cases are given. Calculations have revealed that the final result strongly depends on the combination of porosity and permeability of a reservoir.
Keywords: permafrost; underground storage; natural gas; hydrate formation; mathematical modeling